2016
DOI: 10.1371/journal.pone.0146538
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Bovine Tuberculosis, Cattle Husbandry and Dairy Practices amongst Pastoralists and Small-Scale Dairy Farmers in Cameroon

Abstract: BackgroundControl of bovine tuberculosis (bTB) and zoonotic tuberculosis (zTB) has relied upon surveillance and slaughter of infected cattle, milk pasteurisation and public health education. In Cameroon, like many other sub-Saharan African countries, there is limited understanding of current cattle husbandry or milk processing practices or livestock keepers awareness of bTB. This paper describes husbandry and milk processing practices within different Cameroonian cattle keeping communities and bTB awareness in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 51 publications
2
52
2
Order By: Relevance
“…In fact, cattle remain in the herd for many years and therefore, are more exposed to Brucella infections than sheep. This hypothesis is in agreement with previous observations reporting that as long as infected animals remain in contact with the rest of the herd, the number of infected animals will increase [10,35,36,37].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, cattle remain in the herd for many years and therefore, are more exposed to Brucella infections than sheep. This hypothesis is in agreement with previous observations reporting that as long as infected animals remain in contact with the rest of the herd, the number of infected animals will increase [10,35,36,37].…”
Section: Discussionsupporting
confidence: 93%
“…Remarkably, B. abortus infection rate was signi cantly higher (P <0.0001; X 2 = 46.78) in cattle (17.42%) compared to sheep (1.9%) while B. melitensis was signi cantly (P =0.0008; X 2 = 29.62) more prevalent in sheep. These results could be explained by the fact that B. abortus and B. melitensis are the main etiologic agents of brucellosis in cattle and sheep, respectively [49]. Our results showing high B. abortus infection rate in cattle are in agreement with data of other African countries [12,20,25,50].…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that cattle in contact with buffalo harbour more diverse T. parva parasite populations than cattle from populations that have no recent contact with buffalo (Oura et al, ). A recent study of cattle husbandry and dairy practices among pastoralists and small‐scale farmers in Cameroon indicates that 25% of the herds in the population studied had potentially contacted buffalo during transhumance (Kelly et al, ). This could provide an alternative explanation for the diversity observed in T. parva strains from Cameroon.…”
Section: Discussionmentioning
confidence: 99%